The relationship between prenatal exposure to organophosphate insecticides and neurodevelopmental integrity of infants at 5-weeks of age - Sittiwang, Supattra; Nimmapirat, Pimjuta; Suttiwan, Panrapee; Promduang, Wathoosiri; Chaikittipornlert, Nattapon; Wouldes, Trecia; Prapamontol, Tippawan; Naksen, Warangkana; Promkam, Nattawadee; Pingwong, Sureewan; Breckheimer, Adrian; Cadorett, Valerie; et al. (Frontiers in Epidemiology, 2022)
Organophosphate (OP) insecticides are among the most abundantly used insecticides worldwide. Thailand ranked third among 15 Asian countries in its use of pesticides per unit hectare and fourth in annual pesticide use. More than 40% of Thai women of childbearing age work on farms where pesticides are applied. Thus, the potential for pregnant women and their fetuses to be exposed to pesticides is significant. This study investigated the relationship between maternal urine concentrations of OP metabolites measured during pregnancy and infant neural integrity at 5 weeks of age. We enrolled women employed on farms in our Study of Asian Women and their Offspring’s Development and Environmental Exposure (SAWASDEE) from two antenatal clinics in the Chiang Mai province of northern Thailand. We collected urine samples monthly during pregnancy, composited them by trimester, and analyzed the composited samples for dialkylphosphate (DAP) metabolites of OP insecticides. At 5 weeks after birth, nurses certified in use of the NICU Network Neurobehavioral Scale (NNNS) completed the evaluation of 320 healthy infants. Maternal demographic and health data during pregnancy along with birth data were evaluated as confounders in generalized linear regression models to determine the association between NNNS outcomes and DAP concentrations. After adjusting for confounders and creatinine, we observed a statistically significant inverse association between NNNS arousal and excitability among subjects with increased prenatal DAP concentrations. We identified 3 NNNS profiles by latent profile analysis. Higher prenatal maternal DAP concentrations were associated with higher odds of being classified in a profile indicative of greater self-regulation, but arousal and excitability scores below the 50th percentile relative to US normative samples. This finding is also observed among infants with prenatal exposure to substances of abuse (e.g., methamphetamine). Further evaluations are warranted to determine the implications of these findings for neurodevelopmental outcomes of attention and memory and whether these results imply inadequate responsivity to stimulation among children as they develop.